2021
DOI: 10.47990/alop.v5i2.5
|View full text |Cite
|
Sign up to set email alerts
|

Diagnóstico y manejo de la anquilosis dentoalveolar

Abstract: La Anquilosis Dentoalveolar es una anomalía dental, en la cual se presenta perdida de continuidad del ligamento periodontal, lo que lleva a la unión del hueso alveolar con el cemento o la dentina. Esto impide el proceso eruptivo normal y el crecimiento vertical óseo del diente anquilosado, mientras que los dientes adyacentes siguen su proceso de erupción y crecimiento alveolar normal. Esta situación genera que el diente alterado esté por debajo del plano oclusal, dando la impresión de estar sumergido. La anqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
12

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(16 citation statements)
references
References 20 publications
0
4
0
12
Order By: Relevance
“…This result is similar to existing studies [ 24 , 25 ]. The prevalence of this condition is ten times higher in decidual dentition than in permanent dentition, with a percentage of 1.3–8.9% in children aged 6–10 years in the first stage of mixed dentition, according to the literature [ 10 ]. Zuniga-Tertre et al (2004) observed a maximum prevalence between six to eight years and another study conducted in 2009 by Loriato found the maximum incidence occurred between seven to nine years [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This result is similar to existing studies [ 24 , 25 ]. The prevalence of this condition is ten times higher in decidual dentition than in permanent dentition, with a percentage of 1.3–8.9% in children aged 6–10 years in the first stage of mixed dentition, according to the literature [ 10 ]. Zuniga-Tertre et al (2004) observed a maximum prevalence between six to eight years and another study conducted in 2009 by Loriato found the maximum incidence occurred between seven to nine years [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the theories states that any disruption in the continuity of the periodontal ligament caused by trauma can lead to the onset of the degenerative processes that will result in the fusion between tooth and bone [ 10 ]. If the trauma produced limited lesions, a slight osteoclastic activity will be initiated on the root surface which involves resorption and repair, resulting in healing by depositing new fibers on the cement surface [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Es relativamente común encontrar un molar primario infraocluido que ha dejado de erupcionar verticalmente, en donde el diente permanece por debajo del plano oclusal de los dientes adyacentes. 1,2,4,5,9,12 La infraoclusión es una consecuencia directa de la anquilosis, siendo la anquilosis una anomalía dental que implica la fusión del hueso alveolar con el cemento o la dentina, generando obliteración del ligamento periodontal y pérdida de continuidad de este, puede ocurrir en presencia o ausencia de un diente sucesor permanente afectando el desarrollo óseo porque no sigue un patrón normal vertical de crecimiento, quedando más impactado, deteniendo su crecimiento al mismo tiempo que se detiene la erupción del diente primario 2,4,9,13 . Por otra parte, los dientes anquilosados producen pérdida de longitud del arco por la mesialización del diente adyacente como consecuencia de la pérdida de contacto interproximal.…”
Section: Introductionunclassified